Application and evaluation of interactive virtual technologies in nursing students’ learning and clinical skills assessment. A mixed methods study (Journal of Applied Learning and Teaching, 2024)
Background: During the 2020 iteration of a Bachelor of Nursing Clinical Health Assessment skills course delivered in Singapore, the sudden cancellation of all face-to-face classes due to the pandemic resulted in innovative strategies being quickly created to enable students to successfully complete Objective Structured Clinical Examinations online. However, the realism of the experience was rudimentary. After exploration of a range of technologies, a mixed reality (interactive virtual patient) application was developed within the Microsoft Power Apps platform, implemented and evaluated for the 2022 iteration of the Clinical Health Assessment course.Methods: A mixed methods exploratory design was used with quantitative and qualitative data collected regarding student performance and user experiences.Results: The data suggested positive user experiences, with 60% feeling the application involved them and 80% reporting consistency with real-world experiences. Students’ assessment item results from the 2022 iteration were also compared to previous iterations of the course and showed comparative alignment across the ranges of marks.Conclusion: The mixed reality (interactive virtual patient) application provided a realistic and interactive user experience as well as an effective means of online clinical skills assessment.